Modified polyethylene glycol as a potential material for CO2 capture / Mahsa Sadegh Pour - Mahsa Sadegh , Pour (2019)

(untitled)
Carbon dioxide gas from the utilization of fossil fuel is one of the most significant contributors to greenhouse effect. Absorption process by various solvents is one of the common techniques to capture CO2. Poly ionic liquids (PILs) have shown to be potential solvent for CO2 absorption. Thus, in this work new PILs were synthesized and later used for CO2 absorption process. Two types of water soluble PILs polyethylene glycol-di choline chloride (PEG-(ChCl)2) and polyethylene glycol-di imidazolium iodide (PEG-(mImidI)2) were synthesized. The synthesis was performed through modification of two molecular weights of poly ethylene glycol (PEG); 400 and 600, to be used as solvents for CO2 capture. The synthesized polymers were characterized using 1H-NMR and FT-IR. Presence of choline chloride and methyl imidazolium iodide in the final product were confirmed with 1H-NMR spectra. Moreover, the thermal stability of the prepared polymers were defined by thermal gravimetric analysis and the results showed that the synthesized polymers have high thermal stability. Viscosity and densities of aqueous solutions of modified polymers were also measured. Furthermore, CO2 absorption using the modified poly ionic liquids was conducted at pressures ranging from 10 to 13 bars and temperatures ranging from 30 to 70 ºC. PEG 400-(ChCl)2, PEG 600-(ChCl)2, PEG 400-(mImidI)2 and PEG 600-(mImidI)2 with a concentration of 0.03 M showed CO2 loading of 16.33, 15.53, 18.89 and 18.38 mol CO2/mol PIL respectively. These results showed 20% increase for PEG (400-600)-(ChCl)2 and up to 30% for PEG (400-600)-(mImidI)2 as compared to unmodified PEGs. In order to study on the concentration impact, three different concentration of PEG 400-(mImidI)2 from 0.03 M to 0.1 M were used for CO2 absorption at pressure ranging from 5 to 13 bar and constant temperature. Henry’s constants were also determined and the values obtained at temperature 30 ˚C were 30.11, 28.89, 24.02 and 24.38 for PEG 400-(ChCl)2, PEG 600-(ChCl)2, PEG 400-(mImidI)2 and PEG 600-(mImidI)2, respectively. Enthalpy of the absorption were also obtained and reported. The linear CO2 absorption and decreasing trend for values of heat of absorption confirms the presence of physical CO2 absorption mechanism for the synthesized PILs. In addition, pressure and temperature swing techniques were used to investigate recyclability and regeneration of aqueous polymers and the result showed the synthesized PILs showed great stability on theirs sorption capacity after three cycles of regeneration with only 15% reduction in CO2 loading capacity.